Art therapy practices in museum education: A mini review - Wei, Zhizi; Zhong, Chaofang; Gao, Yunteng (Frontiers in Psychology, 2023)
This article reviews the potential functions and approaches of museum education in alleviating psychological anxiety, particularly the psychological anxiety experienced by adolescents during the COVID-19 pandemic. We outline the main forms of museum education, highlighting how it supports the potential functions of art therapy for psychological anxiety. Thereafter, we review the representative research on museum art therapy practice for different populations to invite discussion, dialogue, and awareness of future directions for museum education and suggest gaps in the research that require further study.